Protecting migrant children's well-being in Ecuador's public schools - Irene Torres; Mariana Pinto-Alvarez; Daniel F. López-Cevallos (Journal of Migration and Health)
Education plays a crucial role in the adaptation and broader societal inclusion of immigrant students and their families. The current study explored the inclusion of migrants in Ecuador's school system as a fundamental tenet of protecting their health and well-being. We conducted a thematic analysis of 13 policy documents, 12 national laws and international agreements, and 31 key informant interviews, applying a human rights lens. We find that, although the 2008 Ecuadorian Constitution and migration laws protect the right of migrants to health and education, key informants argue that these laws are poorly implemented. Furthermore, they agree that the health sector generally does not consider education as a relevant setting for health. In contrast, the public education sector and non-profit organizations at the national and local levels appear to recognize the importance of coordination across the health and education sectors, including school-based initiatives for migrant inclusion.